Nicotinamide is an endogenous agonist for a C. elegans TRPV OSM-9 and OCR-4 channel - Awani Upadhyay; Aditya Pisupati; Timothy Jegla; Matt Crook; Keith J. Mickolajczyk; Matthew Shorey; Laura E. Rohan; Katherine A. Billings; Melissa M. Rolls; William O. Hancock; Wendy Hanna-Rose (Nature Communications, 2016)
TRPV are cation channels activated by physical and chemical stimuli. Here the authors show that nicotinamide is a soluble, endogenous agonist for orthologous TRPV channels fromC. elegans and Drosophila, unveiling a metabolic-based regulation for TRPV channel activity.